Decreases in neprilysin and vasoconstrictors and increases in vasodilators following bariatric surgery. Issue 8 (2nd May 2018) - Ghanim, Husam; Monte, Scott; Caruana, Joseph; Green, Kelly; Abuaysheh, Sanaa; Dandona, Paresh
Abstract : The aim of this study was to determine if weight loss following Roux‐en‐Y gastric bypass (RYGB) surgery in morbidly obese patients is associated with a decrease in plasma concentrations of neprilysin, mediators of the renin angiotensin system (RAS), catecholamines and endothelin‐1, and also with an increase in the concentrations of vasodilators. Fasting blood samples were obtained from 15 patients with morbid obesity and diabetes prior to and 6 months after RYGB surgery. Circulating levels of neprilysin, vasoconstrictors, vasodilators, and the mRNA expression of related genes in circulating mononuclear cells (MNC) were measured. Six months after RYGB surgery the concentrations of neprilysin, angiotensinogen, angiotensin II, renin and endothelin‐1 fell significantly by 27 ±16%, 22 ±10%, 22 ±8%, 35 ±13% and 17 ±6% ( P < .05 for all), respectively, while ANP concentrations increased significantly by 24 ±13%. There was no significant change in aldosterone, BNP, cAMP or cGMP concentrations, or angiotensin converting enzyme (ACE) expression. These changes may contribute to the reduction of congestive cardiac failure and blood pressure risks after RYGB surgery.